Permainan Engklek Terhadap Perkembangan Keterampilan Motorik Dan Kognitif Pada Anak Di Sd Negeri 1 Sukajadi : Permainan Engklek Terhadap Perkembangan Keterampilan Motorik Dan Kognitif Pada Anak Di Sd Negeri 1 Sukajadi - Aziz, Iman; Utami, Lestari; Wardani, Nindi Irma; Azizah, Nurul; Anggraeni, Siti Dewi; Firmansyah, Andan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: One of the traditional games played by two or more children is engklek. The crank game integrates students' motoric and cognitive components; when motor perception is weak, cognitive function becomes less than optimal and optimal. When children play a game, their cognitive abilities in understanding rules, procedures, strategies, tactics and decision making increase. Objective: to determine the effectiveness of the traditional engklek game on children's motoric and cognitive development at SD Negeri 1 Sukajadi, Sadananya District, Ciamis Regency. Method: As an effort to find out the effectiveness of the crank game as an effort to improve motor and cognitive development in SD Negeri 1 Sukajadi students with a total of 6 respondents focused on grade 2 students using observational research methods using the crank game media. This service activity was carried out on May 8 2023 and used a banner with a picture of a crank game box and several broken tiles. Result: there is an increase in children's motor skills and cognitive abilities in the pretest and post-test assessments of the hopscotch game treatment. Before the game was carried out there were still children with motor development who began to develop and after the treatment the children's development entered the criteria for very good development and developed according to expectations. Conclusion: Conclusion: The implementation of community service activities went well according to what was desired and planned. This community service has a positive value for students at SD Negeri 1. This can be seen from the enthusiasm and activeness of the audience or participants in carrying out the crank game activity and the results of the observations made have a good value on the children's motor and cognitive abilities.